Measures of Cooperation for the Electric Power University and Enterprises in Training Vocational Skills for Students - Dan, Nguyen Thi Thanh (VNU JOURNAL OF ECONOMICS AND BUSINESS, 2018)
The purpose of the paper is to research some solutions of cooperation between universities and enterprises in training vocational skills for students. Through the survey on assessment of vocational skills of students and the need for cooperation between Enterprises and Electric Power University, the research proposes some solutions  between two elements of the mechanism of cooperation between University  and Enterprises in training vocational skills for students to ensure graduates can meet the requirements of recruitment agencies as well as the requirements of socio-economic development and employment.